2018
DOI: 10.1007/s10456-018-9602-0
|View full text |Cite
|
Sign up to set email alerts
|

Vascular deficiency of Smad4 causes arteriovenous malformations: a mouse model of Hereditary Hemorrhagic Telangiectasia

Abstract: Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant vascular disorder that leads to abnormal connections between arteries and veins termed arteriovenous malformations (AVM). Mutations in TGFβ pathway members ALK1, ENG and SMAD4 lead to HHT. However, a Smad4 mouse model of HHT does not currently exist. We aimed to create and characterize a Smad4 endothelial cell (EC)-specific, inducible knockout mouse (Smad4f/f;Cdh5-CreERT2) that could be used to study AVM development in HHT. We found that post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 67 publications
8
86
1
Order By: Relevance
“…PI3K/Akt/mTOR pathway to control the AVMs. This observation concurs with recent data obtained in Smad4-deficient mice, which indicate that abnormal PI3K/Akt activation in ECs is primarily controlled by blood flow and not VEGFR2 (24,58). An important question relates to the drug dosing used in this study and whether it allows the administered drugs to reach concentrations within the expected therapeutic range.…”
Section: Discussionsupporting
confidence: 92%
“…PI3K/Akt/mTOR pathway to control the AVMs. This observation concurs with recent data obtained in Smad4-deficient mice, which indicate that abnormal PI3K/Akt activation in ECs is primarily controlled by blood flow and not VEGFR2 (24,58). An important question relates to the drug dosing used in this study and whether it allows the administered drugs to reach concentrations within the expected therapeutic range.…”
Section: Discussionsupporting
confidence: 92%
“…We further found that, although Siro fully inhibited mTOR overactivation in vivo, its anti-AVM effect was only partial and could be significantly potentiated upon VEGFR2 inhibition by Nin, indicating that VEGFR2 can signal independently of the PI3K-Akt-mTOR pathway to control the AVMs. This observation concurs with recent data obtained in Smad4 deficient mice that indicate that abnormal PI3K-Akt activation in ECs is primary controlled by blood flow and not VEGFR2 (24,58).…”
Section: Discussionsupporting
confidence: 93%
“…These are mitochondrial apoptosis, endoplasmic reticulum‐related apoptosis and Fas‐mediated death . Notably, brain tissues contain abundant mitochondria which consistently supply energy to sustain brain function such as neurotransmitters release and neuronal survival . Mitochondrial apoptosis has been reported in the progression of cerebral IRI through a poorly understood mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Notably, brain tissues contain abundant mitochondria which consistently supply energy to sustain brain function such as neurotransmitters release and neuronal survival. 11,12 Mitochondrial apoptosis has been reported in the progression of cerebral IRI through a poorly understood mechanism. 13,14 At reperfusion stage, mitochondria produce the majority of ROS that are generated, and the latter alters the mitochondrial membrane potential.…”
Section: Introductionmentioning
confidence: 99%